FACTORS AFFECTING SHARIAH AUDIT QUALITY IN ISLAMIC BANKING (Comparative Study of Islamic banking in Indonesia and Malaysia in 2017-2020) - Icih Icih; Silvia Marcelina; Asep Kurniawan; Hazelin Falina Binti Rosli (STIESA Press, 2023)
This study aims to determine the differences in the quality of sharia audits in Islamic banking in Indonesia and Malaysia based on the size of the sharia supervisory board, the size of the audit committee, the frequency of audit committee meetings, the reputation of public accounting firms, the specialization of the auditor industry and audit delays in Islamic banking in Indonesia and Malaysia during 2017-2020. This study uses quantitative data with the Mann Whitney U-test method. The results showed that there were differences in the quality of sharia audits in Indonesian and Malaysian Islamic banks based on the size of the sharia supervisory board, the reputation of public accounting firms, the specialization of the auditor industry and audit delays.